(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Currently There is no noninvasive chemical biomarker, available for evaluating volume status, in individuals with endstage kidney disease (ESKD). This study aimed to determine the relationship between copeptin level and volume status in hemodialysis patients. Methods. This clinical trial enrolled 84 patients with ESKD (Mean age ± SD: 54.31 ± 15.47) on maintenance hemodialysis (3-times weekly, 4h /session). Plasma levels of Hb, copeptin, HCT, Na, and BUN, patients’ weight, systolic and diastolic blood pressure and mean arterial pressure were measured, before and after hemodialysis. Age, sex, etiology of kidney failure, and duration of dialysis were also recorded., and the correlation between copeptin level and all variables was evaluated. Results. There was a significant positive correlation between copeptin level and Hb (r = 0.313, P < .05), and HCT (r = 0.25, P < .05), while a negative association was found between copeptin level and Na (r = -0.051, P > .05) and IDWG (r = -0.05, P > .05). Although copeptin concentration was higher in females before (929.23 pmol/L) and after dialysis (783.3 pmol/L) than male patients (657.05 and 697.45 pmol/L), the mean copeptin changes was higher in male (205 pmol/L) than female (197 pmol/L) (P > .05). The level of copeptin decreased (P > .05) but the level of Hb (P < .05), HCT (P < .05), and Na (P > .05) were increased after dialysis compared to pre-dialysis period. Conclusions. Copeptin could be used as a surrogate marker for the diagnosis of volume status in hemodialysis patients. DOI: 10.52547/ijkd.7119